Car wash wastewater treatment using kapok fiber as adsorbent - Ibrahim, Muhammad Shahrul Shafendy (2022)
Generally, cars have been used as main mean of transportation that requires cleaning regularly and will generate the car wash wastewater (CWW). In Malaysia, the CWW is released to the public drain without any treatment and threatened the aquatic livings as it consists of mainly oil and grease (O&G) and anionic surfactant (AS) that contributes to chemical oxygen demand (COD) concentrations and did not comply with Malaysia’s standard discharge limit (industrial effluent). This study proposes an efficient and easily-operated approach to treat the CWW using kapok fibre (KF). The KF has been reported to have high affinity with oils where its lumen structures and lignin layers were reported to be responsible for its efficiency. In order to confirm the importance of lumen structure and lignin, delignification on the KF was done using sodium hydroxide, hydrochloric acid and chloroform. After delignification, the structures of modified- KF (MKF) were found to be crumpled. Moreover, the raw KF (RKF) and MKFs were then used to treat the synthetic CWW to remove the COD, O&G and AS in a batch-scale study. Overall, the RKF performed the best with removal of COD, O&G and AS at 80.8, 100.0 and 24.4 % respectively at the optimum operating pH of 9, the dosage of 1.0 g and a contact time of 30 minutes. Based on the isotherm studies, the adsorption of the COD, O&G and AS onto RKF and MKF were found to lean towards physisorption and chemisorption respectively with the formation of monolayer on the surface. As RKF was more efficient in the batch-scale study, it was then used for the column study to treat real CWW and the removals of COD, O&G and AS were found to comply with the standards. The breakthrough studies of the RKF column indicates the adsorptions are dependent on the influent concentration. Moreover, the reusability of the RKF column was experimented and resulted in excellent performance up to 3 cycles. Overall, the RKF was found to be able to treat CWW efficiently up to 88 %, 100 % and 83 % removals of COD, O&G and AS respectively, thus demonstrating promising potential for real scale application.